FEATURES OF REGULATORY MECHANISMS FOR CAPITAL INTEGRATION IN THE CORPORATE SECTOR (ON THE EXAMPLE OF POLAND) (International Journal of Innovative Technologies in Economy, 2020)
The development of the corporate sector in Poland has become an important element in the formation of a new economic environment and the transformation of social relations. The article analyses the regulatory mechanism in the corporate sector of Poland, which concerns, in particular, the mechanisms of integration and capital development, with the help of the content analysis method. Considerable attention is paid to updating Polish legislation in accordance with the requirements of the European Union (EU). The author carried out a retrospective analysis of the process of the development of market economy in Poland and the place of privatization in it. The study describes significance of privatization processes in Poland for new progressive tendencies of development of public relations. The article analyses the problems that still remain relevant for the development of the corporate sector in Poland. The regulatory features of the activity of transnational companies in modern Poland and their significance for the economy are studied. The author notes the role of Poland’s membership in the EU to ensure further development of the market economy, the development of the corporate sector in it on the basis of capital integration. It is concluded about a significant capitalization of Polish companies. Access of Polish companies to capital is a necessary condition for dynamic development, as small Polish businesses are unable to accumulate investment funds on their own and incur high loan costs.